The tongue coating metabolomic profiling variations of intraoral halitosis subjects - Dr Yu Zhang (Elsevier, 2023)
Aim or Purpose: This study aims to assess the metabolic variations related to intraoral halitosis among periodontally healthy Chinese adults. Materials and Methods: Followingclinical examination, tongue coating samples were collected from 42 periodontally healthy subjects (aged 18-65 years old, 21 subjects with halitosis and 21 subjects without halitosis) who fulfilled the selection criteria. The work was supported by the Ethics Committee at the Ninth People's Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, China. The organoleptic score was used to evaluate the halitosis status. The metabolic profiles were analyzed by liquid chromatograph mass spectrometer combined with bioinformatics and statistical analyses. Data were analyzed using SPSS software (v20, IBM, NY, USA) with the significance level set at 5%. Results: The identification and quantification results of metabolites showed that a total of 2182 metabolites had been detected, of which 1478 were annotated. Multivariate analysis showed a distinct separation between the halitosis patients and healthy controls in positive and negative ions modes, respectively, and in comparisons of halitosis and the control group, 204 metabolites were significantly different in abundance, including histamine, 5-aminosalicylic acid and cyclopentanol. Most of these metabolites were belong to amino acid metabolism, metabolism of cofactors, carbohydrate metabolism and vitamins and biosynthesis of other secondary metabolites, among which paramethasone acetate may act as a biomarker for intraoral halitosis. Conclusions: Halitosis individuals present a unique tongue coating metabolome, which can distinguish them from healthy subjects. We provide a comprehensive view of metabolic characteristic of periodontally healthy halitosis adults, which could help to understand the disease and therapeutic intervention of halitosis.